2023
DOI: 10.1021/acs.jafc.3c02587
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Fungicidal Activity against Rice Sheath Blight of Novel N-Acyl-1,2,3,4-tetrahydroquinoline Derivatives

Abstract: To discover fungicides with novel targets, a series of N-acyl-1,2,3,4-tetrahydroquinoline (NATHQ) derivatives were designed and synthesized by linking the active substructure NATHQ moiety in aspernigerin with the O-benzyl oxime-ether scaffold in commercial agrochemicals. Target compound structures were identified using proton and carbon-13 nuclear magnetic resonance spectroscopies and high-resolution mass spectrometry. Preliminary bioassays indicated that at 40 mg/L, some target compounds exhibited moderate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“… 39 It has shown cytotoxic effects on tumor cell lines and has potential as a pharmaceutical or lead compound. In studies, aspernigerin demonstrated certain fungicidal, insecticidal, and herbicidal properties 40 …”
Section: Resultsmentioning
confidence: 99%
“… 39 It has shown cytotoxic effects on tumor cell lines and has potential as a pharmaceutical or lead compound. In studies, aspernigerin demonstrated certain fungicidal, insecticidal, and herbicidal properties 40 …”
Section: Resultsmentioning
confidence: 99%
“…Plant pathogens seriously affect food security and yield, and the use of fungicides is the most direct and effective way to control crop diseases. , According to FRAC, more than 230 small-molecule fungicides are currently commercialized, providing a guarantee for a global food supply and social security and stability. However, with the long-term use of traditional chemical fungicides, pathogen resistance is becoming more and more serious, and the ecological environment is also under threat. Therefore, the development of new, green, safe, and efficient fungicides is indispensable and also in line with the concept of green sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoctonia solani (R. solani), a major fungal pathogen causing rice sheath blight, poses a significant threat to global agriculture. , It infects various parts of rice plants, leading to substantial yield losses of 10–50%. , In recent years, a variety of unfavorable factors have promoted the occurrence of rice sheath blight, increasing the difficulty of prevention and control, such as unreasonable fertilization, climate change, large-scale cultivation of a single high-yield rice variety, etc. , Additionally, the demand and quality of rice are constantly increasing, whereas the availability of arable land is on the decrease. ,, Therefore, the long-term effective control of R. solani is crucial for the profitability of rice production.…”
Section: Introductionmentioning
confidence: 99%